Quantification of dissolved CO2 plumes at the Goldeneye CO2-release experiment. (July 2021) - Gros, Jonas; Schmidt, Mark; Linke, Peter; Dötsch, Saskia; Triest, Jack; Martínez-Cabanas, María; Esposito, Mario; Dale, Andrew W.; Sommer, Stefan; Flohr, Anita; Fone, Joseph; Bull, Jonathan M.; et al.
Abstract: According to many prognostic scenarios by the Intergovernmental Panel on Climate Change (IPCC), a scaling-up of carbon dioxide (CO2 ) capture and storage (CCS) by several orders-of-magnitude is necessary to meet the target of ≤2 °C global warming by 2100 relative to preindustrial levels. Since a large fraction of the predicted CO2 storage capacity lies offshore, there is a pressing need to develop field-tested methods to detect and quantify potential leaks in the marine environment. Here, we combine field measurements with numerical models to determine the flow rate of a controlled release of CO2 in a shallow marine setting at about 119 m water depth in the North Sea. In this experiment, CO2 was injected into the sediment at 3 m depth at 143 kg d -1 . The new leakage monitoring tool predicts that 91 kg d -1 of CO2 escaped across the seafloor, and that 51 kg d -1 of CO2 were retained in the sediment, in agreement with independent field estimates. The new approach relies mostly on field data collected from ship-deployed technology (towed sensors, Acoustic Doppler current profiler—ADCP), which makes it a promising tool to monitor existing and upcoming offshore CO2 storage sites and to detect and quantify potential CO2 leakage. Highlights: Combination of towed sensors and numerical simulations quantified the CO2 leakage. 64% of CO2 injected at 3-m depth in the sediment leaked into bottom water. Gas-phase measurements of chemical tracers validated the bubble dissolution model.